Kadar Glukosa Darah dan Malondialdehid Ginjal Tikus Diabetes yang Diberi Latihan Fisik - Diyah Candra Anita (Universitas Muhammadiyah Yogyakarta, 2015)
Diabetes Mellitus is a condition characterized by chronic hyperglycemia associated with insulin deficiency. Regular and measurable physical exercise can lower blood glucose levels and increase the endogenous antioxidant defenses, thereby the levels of lipid peroxidation (MDA) can also decrease. The objective of this study was to determine the relation between blood glucose levels and kidney malondialdehyde levels in streptozotocin(STZ)-induced rats which were given physical exercise. This study was purely experimental with group post-test only design. The subjects were 10 STZ-induced male rats of Sprague Dawley strain. Physical exercise was given for 9 weeks using a treadmill. The results of independent t-tests showed that the fasting blood sugar level of the rats was 0.048 and the kidney MDA level was 0.767. Pearson correlation test result of STZ-induced rat group was only 0,799 and that of STZ-induced rats with physical exercise was 0.35. In conclusion, there was no signifi cant correlation between fasting blood glucose levels and kidney MDA levels after treatment.Keywords: Diabetes Mellitus (DM), physical exercise, blood sugar, malondialdehyde, kidney.